Age-Related Macular Degeneration: Insights into Inflammatory Genes - Raffaella Cascella; Michele Ragazzo; Claudia Strafella; Filippo Missiroli; Paola Borgiani; Francesco Angelucci; Luigi Tonino Marsella; Andrea Cusumano; Giuseppe Novelli; Federico Ricci; Emiliano Giardina (Journal of Ophthalmology)
Age-related macular degeneration (AMD) is a progressive neurodegenerative disease that affects approximately 8.7% of elderly people worldwide (>55 years old). AMD is characterized by a multifactorial aetiology that involves several genetic and environmental risk factors (genes, ageing, smoking, family history, dietary habits, oxidative stress, and hypertension). In particular, ageing and cigarette smoking (including oxidative compounds and reactive oxygen species) have been shown to significantly increase susceptibility to the disease. Furthermore, different genes (CFH, CFI, C2, C3, IL-6, IL-8, and ARMS2) that play a crucial role in the inflammatory pathway have been associated with AMD risk. Several genetic and molecular studies have indicated the participation of inflammatory molecules (cytokines and chemokines), immune cells (macrophages), and complement proteins in the development and progression of the disease. Taking into consideration the genetic and molecular background, this review highlights the genetic role of inflammatory genes involved in AMD pathogenesis and progression.